Turbulent boundary layer trailing-edge noise: Theory, computation, experiment, and application. (1st October 2021) - Lee, Seongkyu; Ayton, Lorna; Bertagnolio, Franck; Moreau, Stephane; Chong, Tze Pei; Joseph, Phillip
Abstract: When the pressure fluctuations caused by turbulence vorticity in the boundary layer are scattered by a sharp trailing edge, acoustic energy is generated and propagated to the far field. This trailing edge noise is emitted from aircraft wings, turbomachinery blades, wind turbine blades, helicopter blades, etc. Being dominant at high frequencies, this trailing-edge noise is a key element that annoys human hearing. This article covers virtually the entire landscape of modern research into trailing-edge noise including theoretical developments, numerical simulations, wind tunnel experiments, and applications of trailing-edge noise. The theoretical approach includes Green's function formulations, Wiener–Hopf methods that solve the mixed boundary-value problem, Howe's and Amiet's models that relate the wall pressure spectrum to acoustic radiation. Recent analytical developments for poroelasticity and serrations are also included. We discuss a hierarchy of numerical approaches that range from semi-empirical schemes that estimate the wall pressure spectrum using mean-flow and turbulence statistics to high-fidelity unsteady flow simulations such as Large Eddy Simulation (LES) or Direct Numerical Simulation (DNS) that resolve the sound generation and scattering process based on the first-principles flow physics. Wind tunnel experimental research that provided benchmark data for numerical simulations and unravel flow physics is reviewed. In each theoretical, numerical, and experimental approach, noise control methods for mitigating trailing-edge noise are discussed. Finally, highlights of practical applications of trailing-edge noise prediction and reduction to wind turbine noise, fan noise, and rotorcraft noise are given. The current challenges in each approach are summarized with a look toward the future developments. The review could be useful as a primer for new researchers or as a reference point to the state of the art for experienced professionals.